سلطة الضبط للبريد والمواصلات السلكية واللاسلكية في القانون الجزائري - مــــــــــراد, غــــــــزلان (جامعة الوادي University of Eloued, 2017)
مر قطاع البريد والمواصلات السلكية واللاسلكية بمرحلتين رئيسيتين: مرحلة الاحتكار المنصوص عليها الأمر 75-89 والمتضمن قانون البريد والمواصلات السلكية واللاسلكية ففي هذه المرحلة كانت الدولة هي الممول المباشر والوحيد لنشاطات المواصلات السلكية واللاسلكية، وبهذا كانت خدمات البريد والمواصلات السلكية واللاسلكية عبارة عن خدمة عمومية تقدمها الإدارة للمستخدم. مرحلة فتح المنافسة التي شُرع فيها بمقتضى القانون 2000-03 الذي نص على إدخال آليات السوق في قطاع البريد والمواصلات السلكية واللاسلكية، وإنشاء سلطة ضبط البريد والمواصلات السلكية واللاسلكية. سلطة ضبط البريد والمواصلات السلكية واللاسلكية هي منشأة مستقلة تتمتع بالشخصية المعنوية والسلطة المالية، تتشكل من هيئتين محددتين، وهما: المجلس والمديرية العامة. تمت مراجعة القانون 03-2000 المؤرخ في 5 أغسطس 2000 المحدد للقواعد العامة للبريد والمواصلات السلكية واللاسلكية بموجب قانون المالية لسنة 2015 بحيث يخول لسلطة الضبط للبريد والمواصلات السلكية واللاسلكية تطبيق ترسانة من العقوبات المالية ضد متعاملي البريد والمواصلات السلكية واللاسلكية الذين لا يحترمون التزاماتهم الأساسية. The postal and telecommunications sector has gone through two (02) major stages: The monopoly stage of Ordinance No 75-89 on the Post and Telecommunications Code, during which the State was the direct and sole provider of postal and telecommunications activities. Post and telecommunications were then a public service provided by the administration to the user. The stage of opening to competition initiated by Law 2000-03 which introduced market mechanisms in the postal and telecommunications sector, and The establishment of the Regulatory Authority of the Post and Telecommunications . The Regulatory Authority of the Post and Telecommunications (ARPT) is an independent institution with legal personality and financial autonomy, is composed of a Board and a Director General. The finance law for 2015 revises the law 2000-03 of August 5, 2000 setting the general rules relating to the post and telecommunications by introducing a panoply of pecuniary sanctions in favor of the Regulatory Authority, against the operators postal and telecommunications services that fail to meet their essential obligations
قانــــــون أعمــــــــال
Keywords: الضبط الاقتصادي – المنافسة – سلطة الضبط - الاحتكار – البريد والمواصلات السلكية واللاسلكية – مجلس المنافسة - الاختصاص – التداخل – الدولة الضابطة.; Economic Regulation - Competition - The Regulatory Authority - Monopolies - Post and Telecommunications - Competition Council - Competence - Interferences - Regulatory State